Liquid phase microextraction based sensitive analytical strategy for the determination of 22 hazardous aromatic amine products of azo dyes in wastewater and tap water samples by GC-MS system - Balcik, Utku; Chormey, Dotse Selali; Ayyildiz, Merve Firat; Bakirdere, Sezgin (ELSEVIER, 2020)
Dyes that consist of the azo functional group (ReN]NeR') are classified as azo dyes, which make up a large percentage of commercial dyes. Cleavage of the azo bond could lead to products including some aromatic amines that are harmful (carcinogen) to human beings and other organisms. This study presents a comprehensive optimization and validation of a dispersive liquid-liquid microextraction (DLLME) method for the preconcentration of 22 aromatic amines in gas chromatography spectrometry system. DLLME parameters including dispersive solvent, extraction solvent and salting-out effect were optimized in a univariate approach to obtain optimum conditions of the method. An isotopically labeled compound (bisphenol A D-16) was used as internal standard to enhance the precision (R-2) of calibration plot from 0.9952-0.9994 to 0.9991-0.9999. The limits of detection calculated for the analytes were in the range of 0.17-8.5 mu g/L, corresponding to enhancement in detection powers between 4.0 and 99 folds. Spike recovery experiments were used to validate the optimized method's accuracy and the results obtained for tap water and wastewater samples spiked at different concentrations were in the range of 91-109% and 91-110%, respectively. The recovery results established the method's accuracy and applicability to real samples.
Keywords: Azo dyes; Aromatic amines; DLLME; GC-MS; HUMAN URINE; EXTRACTION; Chemistry